Characterization of an ultraviolet irradiation chamber to monitor molecular photodegradation by Raman spectroscopy. Issue 2 (3rd March 2016) - Bório, Viviane Gadret; Fernandes, Adjaci Uchôa; Silveira, Landulfo
ABSTRACT: A homemade ultraviolet chamber is reported to induce photochemical changes with characterization by Raman spectroscopy. The equipment has compartments for ultraviolet-A (UV-A) (8 lamps of 8 W) and for UV-A + ultraviolet-B (UV-B) irradiation (4 lamps of 26 W and 1 lamp of 15 W). The irradiance was measured 3, 5, and 10 cm from the light sources. The maximum irradiance was obtained at 3 cm (UV-A: 2.66 mW/cm 2 and UV-A + UV-B: 4.30 mW/cm 2 ). The chamber internal temperature was stabilized at 30°C after 1 hr of operation with an internal relative humidity of approximately 45%. 10% Collagen was irradiated with UV-A at 2.0 mW/cm 2 for 3 hr with changes in Raman peaks at 1253, 1271, 1453, and 1660 cm −1 indicating changes in conformation. 5% Atenolol was irradiated with UV-A + UV-B at 4.30 mW/cm 2 for 8 hours with changes to Raman peaks at 822, 1186, 1206, 1248, and 1618 cm −1 . A commercial insect repellent was irradiated with UV-A + UV-B at 4.30 mW/cm 2 for 8 hr and decreases in Raman intensity were observed at 526, 690, 1003, and 1606 cm −1 due to degradation of N, N-diethyl-m-toluamide. The results demonstrate proper operation of the irradiation chamber with Raman spectroscopic monitoring.